Influence of extraction solvent on phenolic content and antioxidant capacity level of a commercial food supplement from Moringa oleifera leaves - Urías-Orona, Vania; Gutiérrez-Soto, Guadalupe; Ruiz-Bautista, Jahir; Flores-Alonso, Raúl; Montiel-Ramos, Isac; Martínez-Ávila, Guillermo C. G.; Aranda-Ruiz, Juana; Niño-Medina, Guillermo (Archivos Latinoamericanos de Nutrición (ALAN), 2020)
The objective of this research was to evaluate the effect of extraction solvent on phenolic compounds content (total phenols, total flavonoids) and antioxidant capacity levels (DPPH, ABTS and FRAP) of a commercial food supplement from Moringa oleifera leaves. The content of total phenols, total flavonoids and total non-flavonoids ranged from 55.98 to 226.20 mg ChlAE/g, from 17.63 to 23.46 mg CatE/g and from 38.34 to 202.73 mg CatE/g mg/g, respectively, while condensed tannins were not detected in none of the extracts. Non-flavonoids compounds were the most abundant group of phenolics in all the extracts ranging from 68 to 90% of the total phenols content. Levels of antioxidant capacity ranged from 22.43 to 124.93, 101.03 to 245.25 and 77.06 to 214.17 μmolTE/g in ABTS, DPPH and FRAP, respectively. In addition, EtOH 50% and EtOH 100% extracts showed the highest and lowest content in phenolics content and antioxidant capacity level. Finally, data obtained in the content of phenolics and antioxidant capacity levels of the present study are higher than most of data of scientific literature reported previously by other authors. El objetivo de esta investigación fue evaluar el efecto del solvente de extracción en el contenido de compuestos fenólicos (fenoles totales, flavonoides totales) y los niveles de capacidad antioxidante (DPPH, ABTS y FRAP) de un suplemento comercial de hojas de Moringa oleifera. El contenido de fenoles totales, flavonoides totales, no-flavonoides totales oscilaron de 55.98 a 226.20 mg ChlAE/g, de 17.63 a 23.46 mg CatE/g y de 38.34 a 202.73 mg/g, respectivamente, mientras que no fue detectada la presencia de taninos condensados en ninguno de los extractos. Los compuestos fenólicos noflavonoides fueron el grupo más abundante de compuestos fenólicos en todos los extractos y oscilaron de 68 a 90% del total de los fenoles totales. Los niveles de capacidad oscilaron de 22.43 a 124.93, de 101.03 a 245.25 y de 77.06 a 214.17 μmolTE/g en ABTS, DPPH y FRAP, respectivamente. Además, los extractos con EtOH 50% y EtOH 100% mostraron el contenido más alto y más bajo de fenólicos y niveles de capacidad antioxidante, respectivamente. Finalmente, los datos obtenidos en el contenido de compuestos fenólicos y los niveles de capacidad antioxidante del presente estudio son más altos que la mayoría de los datos reportados previamente en literatura por otros autores.